The Role of Digital Marketing in Promoting Private Universities in the Covid-19 Pandemic Period : A Phenomenological Approach - Diana Prihadini,; Siti Nurbaity,; Heksawan Rachmadi,; Krishantoro, (Technium Social Sciences Journal, 2020)
This study aims at answering the question of how the experiences of each university in carrying out their marketing activities, especially during the COVID-19 pandemic, what are the difficulties when they implement digital marketing and how do they get students after doing digital marketing. In this study, the phenomenological approach of the qualitative research design was employed. The data collection was carried out by semi-structured interviews to dig deeper into the experiences of informants consisting of 20 marketing representatives from private universities in the areas of Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek). This research shows that digital marketing is an important factor to be able to promote private universities and get students during the Covid 19 pandemic. It is also very important to recruit skilled staff on IT. We can see a very significant difference between campuses that have experts to carry out digital marketing and those that don't. This can also be seen from the percentage of the number of students admitted during the Covid-19 pandemic, where the number of students enrolling in colleges with professional digital marketing did not show a decrease but on the contrary, there was a significant increase in the era of the Covid-19 pandemic.